Tratamiento Tributario y su efecto en la rentabilidad del sector pesquero - Pazmiño Caymayo, Gabriela del Rocío (2021)
The Ecuadorian fishing sector plays a fundamental role in the country's economy, where the inadequate tax treatment that occurs in the sector influences its low profitability by not correctly determining the taxes caused in each period, these generate a value to pay unreal, many times this has caused a higher payment by not applying the tax regulations correctly. The objective of this research was to analyze the tax treatment and examine the tax items that influence the calculation of income tax, which made it possible to determine the tax factors that influence the profitability of the sector……….